Understanding South Korean women workers’ career transition experiences: using the career decision tree model - Kim, Namhee; Kim, Kyung Nam; Baek, Pyounggu (Frontiers in Psychology, 2024)
The reasons for South Korean women workers' career transitions and influencing factors were explored using a qualitative approach with in-depth interviews with 35 South Korean women workers at various career stages. Based on Bian and Wang's Career Decision Tree Model (2019) as a conceptual framework, a context-sensitive interpretation of South Korean women workers' unique career transition experiences was conducted. Their main motive of career transitions was difficulty maintaining their physical and mental health, which stemmed from their demanding work life. A typical issue, the burden of child rearing and family responsibilities, was also reported, but it was not the primary reason for their career transitions. Instead, the women workers often mentioned these responsibilities along with other reasons. Other reasons were unresolved career interests and expectations associated with their lack of career goals and preparation prior to joining the labor market. These factors led to significant changes in women's values and priorities along their career path, which finally triggered a decision to make a career transition. South Korean socio-cultural characteristics embedded in the South Korean women's personal and organizational lives provide insights on how to interpret the findings. Although on the surface some of our findings appeared to confirm previous studies on women's career transitions in Western-based literature, noteworthy differences were discovered when delving deeper into women's career transitions in the South Korean context.